1990
DOI: 10.1111/j.1349-7006.1990.tb02682.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Distribution of Subjects Seropositive for Human T‐Cell Leukemia Virus Type 1 in Papua New Guinea

Abstract: Of 1471 sera collected from 1986 to 1989 in Papua New Guinea (PNG), 2.2% were found to be positive for anti‐HTLV‐1 antibody by successive particle agglutination and immunofluorescence tests. The seropositive rate varied in different provinces and was higher in the coastal areas of the main island and in neighboring small islands than in the highlands of PNG. The frequency of HTLV‐1 infection of children was higher, but the age‐dependent increase in antibody positivity, generally observed in other HTLV‐1 endemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Specifically, although most highland populations in Papua New Guinea, first discovered by the outside world between the 1930s and 1960s, are completely seronegative for HTLV-I infection (2,8,9), at least one isolated group, the Genatei, is highly seropositive (8) (Melanesia 1-6). The respective sequences of HTLV-IIC344/Mo (24) and STLV-Imacaque (25) (22, 33, 34).…”
Section: Gp46 -Gp21mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, although most highland populations in Papua New Guinea, first discovered by the outside world between the 1930s and 1960s, are completely seronegative for HTLV-I infection (2,8,9), at least one isolated group, the Genatei, is highly seropositive (8) (Melanesia 1-6). The respective sequences of HTLV-IIC344/Mo (24) and STLV-Imacaque (25) (22, 33, 34).…”
Section: Gp46 -Gp21mentioning
confidence: 99%
“…High prevalences of antibodies against human T-lymphotropic virus type I (HTLV-I) have been reported for several coastal and inland Melanesian populations by using screening tests such as enzyme immunoassay and gelatin particle agglutination (1)(2)(3)(4)(5)(6)(7)(8)(9). These reported high prevalences of antibodies against HTLV-I, however, have been viewed with skepticism by some investigators because of the failure of such Melanesian sera to neutralize a prototype strain of HTLV-I (10).…”
mentioning
confidence: 99%
“…Since the majority of these subjects came from various tribes on the Java and Sumatra Islands (west Indonesia), we concluded that there was a very low seroprevalence of positivity to HTLV-I in Jakarta which may also be low in western parts of Indonesia. The incidence of HTLV-I infection in eastern parts of Indonesia may be different from Jakarta since in this region close to Papua New Guinea a relatively high incidence of HTLV-I infections had been reported [6][7][8]. Further investigation is necessary in the eastern region to establish the entire prevalence of HTLV-I infection in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…tries have shown a distinct geographic cluster of HTLV-I and its associated diseases in South Western Japan [2], the Carribean basin [3] and Central Africa [4,5]. Several studies have found a relatively high incidence of HTLV-I carriers in Papua New Guinea [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…HTLV-I infection, as verified by strict Western blot criteria, is also highly prevalent among the Hagahai, a small hunter-horticulturalist group living in the fringe highlands of Papua New Guinea, and among unrelated individuals from widely separated regions of the Solomon Islands . The recent isolation of genetically distinct, highly divergent sequence variants of HTLV-I from HTLV-I Western blotpositive inhabitants of Papua New Guinea and the Solomon Islands (Gessain et al, 1991 ;Yanagihara et al, 1991b, d, e;Sherman et aL, 1992), viewed within the context of seroepidemiological studies (Kazura et al, 1987;Asher et at., 1988;Garruto et al, 1989Garruto et al, , 1990Armstrong et al, 1990;Imai et al, 1990;Sanders et al, 1990;Yanagihara et aL, 1990Yanagihara et aL, , 1991a, establishes the endemicity of HTLV-I in Melanesia.…”
Section: Introductionmentioning
confidence: 99%